Lipomas of the Internal Auditory Canal and Cerebellopontine Angle. (January 2014) - Bacciu, Andrea; Di Lella, Filippo; Ventura, Elisa; Pasanisi, Enrico; Russo, Alessandra; Sanna, Mario
Objectives: Lipomas of the internal auditory canal (IAC) and cerebellopontine angle (CPA) are exceedingly rare lesions. The purpose of this report was to describe our experience with lipomas of the IAC and CPA and perform a review of the literature. Methods: We report 8 cases of lipomas involving the IAC and/or the CPA that were managed at Gruppo Otologico between April 1987 and October 2012. Results: Four cases of entirely intracanalicular lipomas were radiologically misinterpreted as vestibular schwannomas and underwent tumor removal by a translabyrinthine approach. Two of these patients experienced postoperative facial nerve palsy. Lipomas were suspected in 4 patients on the basis of imaging findings and were managed conservatively. Of these 4 cases, 3 did not show any growth after an average period of 28 months, and 1 case demonstrated tumor growth on follow-up imaging. Conclusions: Neuroimaging represents an extremely important tool for this diagnosis. Attempts to achieve complete resection may result in severe neurologic sequelae, especially in large lesions. Observation with repeated imaging in order to detect growth of the lesion is usually recommended. Debulking of the tumor, mainly aimed at brain stem and cranial nerve decompression, should be considered in cases of disabling and uncontrolled neurologic symptoms and signs.